Combined 3-O-acetylbetulin treatment and carbonic anhydrase IX inhibition results in additive effects on human breast cancer cells. (5th January 2021) - Petrenko, Marina; Güttler, Antje; Funtan, Anne; Keßler, Jacqueline; Emmerich, Daniel; Paschke, Reinhard; Vordermark, Dirk; Bache, Matthias
Abstract: Hypoxia plays a key role in tumor progression and resistance to radiotherapy. Expression of the transmembrane-tethered enzyme carbonic anhydrase IX (CA IX) is strongly induced by hypoxia. High CA IX expression levels correlate with poor prognosis in cancer patients. Previously, we showed that the downregulation of CA IX expression by siRNA interference and the inhibition of CA IX activity results in increased cytotoxicity, inhibition of migration and radiosensitization of hypoxic cancer cells. Betulinic acid (BA) is a natural compound derived from birch bark. It has shown promising anti-tumor effects due to its cancer cell specific cytotoxic properties. We have shown that BA inhibits the HIF-1α pathway, resulting in apoptosis, inhibition of migration and enhanced cytotoxicity of breast cancer cells. In this study, we investigate the effects of the novel betulin derivative 3- O -acetylbetulin (3-AC) and carbonic anhydrase inhibitors (CAI) octyl disulfamate (OCT) or 4-(3-[4-fluorophenyl]ureido)benzenesulfonamide (SLC-0111), on cellular and radiobiological parameters in MDA-MB-231 and MCF-7 cells. Treatment with 3-AC or OCT alone only caused moderate cytotoxicity, reduction in cell migration, ROS production and DNA damage. However, the combined treatment with 3-AC and CAI strongly enhanced radiosensitivity, increased cytotoxicity, inhibited cell motility and enhanced DNA damage. Our findings suggest that the combination of two bioactive drugs 3-AC and a CAI, such as OCT or SLC-0111, could be a promising therapeutic approach for targeting hypoxic tumor cells. Highlights: CA IX downregulation results in sensitivity of hypoxic cancer cells. Betulinic acid induces apoptosis and enhanced cytotoxicity of breast cancer cells. Treatment with betulin derivative (3-AC) and carbonic anhydrase inhibitor (OCT). Combined 3-AC and OCT cause enhanced radiosensitivity, cytotoxicity and DNA damage.